HUBUNGAN INDIKATOR MUTU PELAYANAN DENGAN TINGKAT KEPUASAN PASIEN POLI KESEHATAN IBU DAN ANAK DI PUSKESMAS PLUS PERBAUNGAN - Satria, Beni (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Health services was one of the main factors affected the health status of the community. The organization of health care providers such as community health centers was aform of health resources provider have quality service in appropriate with community expectations. The aim of this research was to known the correlation between the indicators quality of service (technical competence, access to service, human intercourse, security, convenience, continuity of service, efficiency and effectiveness) with the patient health maternity and child health (KIA) level at community health center Plus Perbaungan. The type of research use was quantitative research with cross sectional design. The number of samples of 48 respondents conducted by using accidental sampling technique. The data collection used questionnaires. Data were analyzed quantitatively with Chi-Square test with 95% Î±=0,05 and logistic regression p=0,25. Data analysis showed 5 service quality indicator that related to patient satisfaction of KIA that is technical competence (p = 0,024), relation between man (p = 0,020), comfort (p = 0,024), service continuity (p = 0.027), efficiency (p = 0.003). From 7 variables that enter into logistic regression test there was 1 variable have p value â‰¤ (0,05) that was efficiency variable with value (p = 0,003, B = 1,732) concluded that there is effect of efficiency to satisfaction of patient KIA with big influence 1,732 meaning Efficiency variables 1,732 times affect patient satisfaction KIA. It was expected that the Plus Plus Community Health Center improves the quality of service in order to maintain patient satisfaction especially pay more attention to efficiency services.